LINC00152 acts as a competing endogenous RNA of HMGA1 to promote the growth of gastric cancer cells. Issue 2 (11th January 2022) - Chen, Jiayi; Zheng, Qingfang; Liu, Fang; Jin, Han; Wu, Xiaoyue; Xi, Yang
Abstract: Background: Long noncoding RNAs (lncRNAs) play important roles in almost every stage of cancer development. Given the competing endogenous RNA (ceRNA) hypothesis for the regulation of gene expression, we investigated the role of LINC00152 as a ceRNA in gastric cancer (GC) cells. Methods: Gastric cancer cell lines were used in this study. Mimics of miRNAs and siRNA were used to evaluate the interaction between LINC00152 and HMGA1 . The quantitative real‐time polymerase chain reaction was performed for analyzing gene expression at the transcriptional level. Flow cytometry assay of cell cycle and western blot analysis of related protein expression levels were performed. Online databases such as TCGA and TIMER were used to determine the possibility of HMGA1 and LINC00152 as GC markers and their role in immune infiltration. Results: Treating GC cell lines with LINC00152  siRNAs downregulated the expression of HMGA1 . The cell cycle was arrested in the S phase following a reduction in LINC00152 or HMGA1 expression, whereas the expression of the cell cycle inhibitor P27 increased. In this study, we showed that acting as a ceRNA of HMGA1, LINC00152  has the same function as HMGA1, considering that it could control the cell cycle and promote GC cell proliferation. The TCGA database showed that LINC00152  might be used as a diagnostic marker for GC. Conclusions: These findings provide mechanistic insights into the role of LINC00152 as a ceRNA to regulate HMGA1 expression in GC cells, where it can promote the proliferation of the GC cells by regulating the expression of the P27 . Abstract : Given the hypothesis of ceRNA in the gene expression regulation, we investigated the role of LINC00152 as a ceRNA of HMGA1. LINC00152 and HMGA1 formed the ceRNA network with miR15a and Let 7a, and reciprocally regulated. Down‐regulate the expression of LINC00152 and HMGA1 can arrest the cell cycle by regulated the expression of the P27, and inhabit the proliferation in GC cell.